2005
DOI: 10.1111/j.1365-3164.2005.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, immunological and histopathological findings in a subpopulation of dogs with pododermatitis

Abstract: Clinical, immunological and histopathological findings in 20 adult dogs of varying breeds with chronic (>or=6 months) inflammation confined to the pedal skin were compared over a 2-year period with those of a group of age-matched controls (n=20). All affected dogs were pruritic but systemically well. Lesions were present on all four feet in 18/20 cases. Affected feet were characteristically erythematous, swollen, painful and alopecic. Sinus tracts were evident in 4/20 dogs. Despite a methodical series of diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
2
20
0
2
Order By: Relevance
“…suggested that the severity of the inflammatory response could explain the enhanced expression of IL‐6 mRNA in dogs with anal furunculosis, a theory that is also potentially applicable to dogs with ImR‐LPP. In addition, based on the clinical signs previously reported for this condition, 5 the role of IL‐6 in skin repair 46 may have been a factor underpinning the increased transcript levels recorded in this study.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…suggested that the severity of the inflammatory response could explain the enhanced expression of IL‐6 mRNA in dogs with anal furunculosis, a theory that is also potentially applicable to dogs with ImR‐LPP. In addition, based on the clinical signs previously reported for this condition, 5 the role of IL‐6 in skin repair 46 may have been a factor underpinning the increased transcript levels recorded in this study.…”
Section: Discussionsupporting
confidence: 52%
“…The authors previously proposed the term immunomodulatory‐responsive lymphocytic–plasmacytic pododermatitis (ImR‐LPP) to denote a subpopulation of dogs with idiopathic disease 5 . Affected individuals were systemically healthy but had persistent (≥ 4 months) inflammation and pruritus confined to the pedal skin.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus pseudintermedius is the major cause of canine pyoderma. Furthermore, S. pseudintermedius is also frequently isolated from canine ear and wound infections, and can be a complicating factor in immunomodulatory‐responsive lymphocytic–plasmacytic pododermatitis 71,113,114 . Additionally, it is the staphylococcal species most commonly isolated from canine urinary tract infection 115–117 .…”
Section: Pathogenicitymentioning
confidence: 99%
“…However, in some cases, despite a thorough work up, a specific cause remains elusive. One study reported success in using ciclosporin to treat idiopathic pododermatitis in seven dogs (Breathnach and others 2005). …”
Section: Chronic Pododermatitismentioning
confidence: 99%